2023
DOI: 10.1039/d3fo00489a
|View full text |Cite
|
Sign up to set email alerts
|

Dangshen Huangjiu prevents gastric mucosal injury and inhibits Akt/NF-κB pathway

Qiaohong Xu,
Fang Cui,
Xiaodong Li
et al.

Abstract: One of the top ten tonic herbs, dangshen is frequently found in Chinese functional foods. With the inclusion of dangshen in the list of food and medicine substances in 2020,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 36 publications
2
9
0
Order By: Relevance
“…The threshold concentration was determined to be above 60% for cell viability. 14 As demonstrated in Figure 2A, the viability of GES-1 cells showed a dose-dependent decrease under MNNG treatment up to 120 μM, and the results showed that an MNNG solution of 20 μM and at a time of 24 h produced the most optimal outcomes, which echoed the recent research. 20 Next, the impact of various concentrations of Rg1 on the viability of GES-1 cells for 24, 48, and 72 h was examined.…”
Section: Protective Effect Of Rg1 On Ges-1 Cells Induced By Mnng+nige...supporting
confidence: 76%
See 1 more Smart Citation
“…The threshold concentration was determined to be above 60% for cell viability. 14 As demonstrated in Figure 2A, the viability of GES-1 cells showed a dose-dependent decrease under MNNG treatment up to 120 μM, and the results showed that an MNNG solution of 20 μM and at a time of 24 h produced the most optimal outcomes, which echoed the recent research. 20 Next, the impact of various concentrations of Rg1 on the viability of GES-1 cells for 24, 48, and 72 h was examined.…”
Section: Protective Effect Of Rg1 On Ges-1 Cells Induced By Mnng+nige...supporting
confidence: 76%
“…Oxidative stress is a significant contributing cause to the development of stomach mucosal damage. 14 The results (Figure 7E−G) demonstrated that, in the model group, SOD levels were significantly lower while MPO and MDA levels were significantly higher than those of the control group. Following Rg1 treatment, oxidative stress levels were significantly decreased, as evidenced by the much lower levels of MDA and MPO and the significantly higher levels of SOD, especially the high-dose Rg1 group.…”
Section: Rg1mentioning
confidence: 88%
“…Additionally, prior laboratory investigations have substantiated the gastroprotective properties of DSHJ in preventing gastric mucosal damage. 35…”
Section: Results Of Total Phenol Content Determination Of Low-ba Dshjmentioning
confidence: 99%
“…The results showed that the combination of CP drugs mainly acted in the treatment of cardiovascular system, nervous system, tumor-related, digestive system, metabolic system and other diseases. In the drug therapy involved in CP not only relieves the symptoms of gastritis ( Xu Q. et al, 2023 ), but also blocks the progression of gastritis to gastric cancer ( Weng et al, 2023 ). CP has been used as an important component in the treatment of breast cancer ( Xu et al, 2024 ), gastric cancer ( Xu J. et al, 2023 ), and non-small cell lung cancer ( Hao et al, 2015 ) for many years as an adjuvant therapy ( Chen G. et al, 2024 ).…”
Section: Subsections Relevant For the Subjectmentioning
confidence: 99%
“…TNF-α belongs to the TNF ligand superfamily, which is mainly secreted by macrophages and lymphocytes ( Yuk et al, 2024 ), and promotes the production and secretion of IL-1β and IL-6. TNF-α regulates imbalances in immune regulation ( Deng et al, 2020 ), inflammation ( Xu Q. et al, 2023 ), cancer ( Zhu et al, 2019 ), memory disorders ( Ren et al, 2022 ) and other diseases. In Xu et al’s study, Dangshen Huangjiu (DHJG) achieved the efficacy of preventing gastric mucosal injury by elevating SOD and decreasing MDA, increasing antioxidant capacity, and inhibiting the AKT/NF-κB signaling pathway to decrease the expression of inflammatory factors TNF-α, IL-1β, and IL-6 in the chronic non-atrophic gastritis model of Wistar rats ( Xu Q. et al, 2023 ).…”
Section: Subsections Relevant For the Subjectmentioning
confidence: 99%